GAMBARAN KEPEMILIKAN JAMBAN DI DESA PESODONGAN KECAMATAN KALIWIRO KABUPATEN WONOSOBO TAHUN 2020 - Dwi Atin Faidah (Jurnal Ilmiah Medsains, 2020)
The results of Basic Health Research (Riskesdas) in 2018 showed that the number of households in Indonesia using latrines is 88,2%. One of the districts in Central Java whose coverage of access to healthy latrines is still lowest is Wonosobo district (58%). The purpose of this study was to find out the description of ownership of latrines in Pesodongan Village, Kaliwiro Sub-District. This research is a descriptive study with a cross sectional research design approach. The study was conducted in April-May 2020. The sample in this study was 596 families. Data collection is done through secunder data from Kaliwiro Public Health Center. The data is processed through the process of cleaning, editing, coding, tabulating and entry and then performed statistical analysis using SPSS version 19.0. The statistical design used is univariate analysis. The results showed that the most respondents have permanent healthy latrines are in Pesodongan Hamlet (52,7%), the most respondents have semi-permanent healthy latrines are in Gintung Hamlet (62,5%), the most respondents who share latrines are in Pesodongan Hamlet (42,9%) and most respondents who still have open defecation behavior are in Majaina Hamlet (49,1%). It is hoped that the government will expected to be able to do more intensive triggering and provide assistance in the form of latrines that meet the requirements for residents who do not have latrines.